9 Long term results in real world ablation index guided pulmonary vein isolation – 5 years of follow-up from the MPH AF ablation registry. (6th October 2022) - Fitzpatrick, N; Herczeg, S; Hong, K; Mittal, A; Boles, U; Jauvert, G; Keaney, J; Keelan, E; O'Brien, J; Seaver, F; Galvin, J; Széplaki, G
Abstract : Introduction: Catheter ablation (CA) for symptomatic atrial fibrillation (AF) offers the best outcomes for patients in terms of freedom from AF and carries a IA recommendation from the ESC for drug refractory symptomatic AF. Despite current best techniques a significant proportion of patients suffer a recurrence of atrial arrhythmias post CA, hence there is scope to potentially improve outcomes both in terms of technical aspects of the procedure as well as patient selection. Ablation Index TM (AI, Biosense Webster, Inc., Diamond Bar, CA, USA) is one such technical innovation, it combines contact force, power and time to give a numerical value intended to guide operators in creating safe, durable and transmural ablation lesions. Although AI is widely used, little data has been published on the long-term results of AI guided pulmonary vein isolation (PVI). Here for the first time, we present real world 5-year follow-up data of AI guided PVI. Methods: We performed a retrospective study of 123 consecutive patients who underwent AI guided PVI shortly after its introduction to routine practice starting in late 2016 at our centre ( table 1 ). The study inclusion criteria were wide and allowed for both paroxysmal and persistent patients as well as PVI 'plus' procedures. Patients were excluded if not due to be followed at out centre, as were patients with prior cardiac surgery or left atrial ablation. Data was collected via the MPH AF Ablation Registry and ethical approval was given by the MMUH/MPH IRB. All statistical analyses were performed in R version 4.1.2. Results: The patients studied in this cohort tended to be older, with higher BMI, have greater CHA2DS2-VASc scores and larger left atrial sizes when compared to similar previously published cohorts, while gender balance and other characteristics were similar [1 – 3]. The probability of freedom from atrial arrhythmia at 1–5 years is as follows (number at risk in brackets): Year 1: 0.95(110), Year 2: 0.90(86), Year 3: 0.81(57) and Year 4: 0.70(31) (note the number at risk falls below 10% of the original cohort at 5 years). 54 (43%) of patients were on a class Ic/III anti-arrhythmic drugs (AAD) prior to ablation, only 10(8%) of patients continued their AAD after the blanking period (3 months). Table 2 describes the number of procedures; the lesions sets and other procedural details. 100% of patients achieved acute procedural success. 1.6% was the major complication rate (phrenic nerve injury, pericarditis requiring pericardiocentesis). Univariate and multivariate regression analysis were performed on the following covariates – age, gender, paroxysmal versus persistent AF, components of the CHA2DS2-VASc score, LA size as measured on CT and BMI. Age > 75 (p=0.013HR 2.8 CI 1.6–6.4) and BMI > 35 (p=0.02 HR 2.9 CI 1.2–7) were statistically significant independent predictors of recurrent AF. Notably there was no difference between paroxysmal and persistent AF types ( figures 1 and 2 ). Conclusion: Ablation index guided pulmonary vein isolation is a safe and effective treatment for atrial fibrillation with 95% of patients remaining free from atrial arrhythmia at one year and with a low major complication rate 1.6%. Even with high success rates, challenges remain and in this series age > 75 and BMI > 35 were associated with higher recurrence rates.